Maximizing the Impact of e-Therapy and Serious Gaming: Time for a Paradigm Shift - Fleming, Theresa M.; de Beurs, Derek; Khazaal, Yasser; Gaggioli, Andrea; Riva, Giuseppe; Botella, Cristina; Baños, Rosa M.; Aschieri, Filippo; Bavin, Lynda M.; Kleiboer, Annet; Merry, Sally; Lau, Ho Ming; et al. (Frontiers in Psychiatry, 2016)
Internet interventions for mental health, including serious games, online programs and apps, hold promise for increasing access to evidence-based treatments and prevention. Many such interventions have been shown to be effective and acceptable in trials; however, uptake and adherence outside of trials is seldom reported, and where it is, adherence at least, generally appears to be underwhelming. In response, an international Collaboration On Maximizing the impact of E-Therapy and Serious Gaming (COMETS) was formed. In this perspectives paper, we call for a paradigm shift to increase the impact of internet interventions towards the ultimate goal of improved population mental health. We propose four pillars for change: 1. Increased focus on user-centered approaches, including both user-centered design of programs and greater individualization within programs, with the latter perhaps utilizing increased modulariziation. 2. Increased emphasis on engagement; utilizing processes such as gaming, gamification, telepresence, and persuasive technology. 3. Increased collaboration in program development, testing and data sharing, across both sectors and regions, in order to achieve higher quality, more sustainable outcomes with greater reach. 4. Rapid testing and implementation, including the measurement of reach, engagement and effectiveness, and timely implementation. We suggest it is time for researchers, clinicians, developers and end-users to collaborate on these aspects in order to maximize the impact of e-therapies and serious gaming.